The influence of Palm Kernel Cake and Rice Bran Fermentation Product Mixture to the Broiler Carcass Quality - Yadi Priabudiman; Yana Sukaryana (International Journal of Science and Engineering, 2011)
The purpose of this research was to study the effect of the use of palm kernel cake (PKC) and rice bran (RB) fermentation products mixture to the percentage of broiler carcass weight pieces. Research using completely randomized design (CRD) with treatments of the fermentation product usage rate of   0% (P0), 10% (P1), 20% (P2), 30% (P3) and 40% (P4) of the total ration of 4replications.  Variables measured were percentage of carcass weight ratio cut    pieces  of carcass weight (carcass front, rear carcass, breast meat, wings, back, and thigh) with carcass weight multiplied by 100%. The results showed that the percentage of carcass weight piece front and rear carcass was shown at P3.